Social Work with Individuals Having Alcohol Usage Problems: Overview of the Situation in Lithuania - Kievišienė, Justina (Socialinė teorija, empirija, politika ir praktika, 2021)
This article analyzes social work with individuals having alcohol usage problems in Lithuania. In this survey-based quantitative research, frequency data was gathered to examine the usage of methods, services, practices and challenges in this specific area. The results revealed a strong orientation towards individual intervention in social work with individuals having alcohol usage problems. Uncommon usage of group, community or network methods was observed in research data. Low usage of social action or social welfare methods might represent a weak policy-making function. Among services, providing information, consultation and representation are the most often applied. Lithuanian social workers also favor social skills development and family consultation in terms of specific practices, as those are the most often used. Finally, professionals acknowledge that low the motivation among clients to change is among the biggest challenges in this field. Improvements in social work with individuals having alcohol usage problems could be made through the enhancement of skills and practices that are the most effective in the substance abuse area, although relatively rarely used in social work in Lithuania.
Keywords: social work; alcohol usage; services; practices